Isozyme variation in Passiflora subgenera Tacsonia and Manicata. Relationships between cultivated and wild species - Segura, Sergio D.; Coppens d'Eeckenbrugge, Geo; Ocampo Nahar, César H.; Ollitrault, P (Springer, 2003)
Isozyme variation was studied in 87 plants from 32 cultivated and wild accessions of banana passion fruit (P. tripartita var. mollissima, P. tripartita var. tripartita, P. tarminiana, and P. mixta), rosy passion fruit (P. cumbalensis), tin-tin (P. pinnatistipula), gulián (P. ampullacea), P. antioquensis, P. bracteosa, and P. manicata, from the Andes of Venezuela, Colombia, and Ecuador. Six polymorphic enzyme systems (IDH, PGDH, PGM, DIA, PRX, and ACP) revealed 31 zymotypes characterized by the presence or absence of 31 electromorphs. Cluster analysis separated clearly the accessions of P. tarminiana, P. tripartita, P. mixta, and P. cumbalensis from the less typical species of subgenus Tacsonia, which is consistent with morphological evidence. P. mixta showed the highest intraspecific variation and the closest affinity with P. tripartita. The accessions of these two species formed two clusters, one dominated by Colombian genotypes and the other dominated by Ecuadorian genotypes. One of the P. tripartita var. mollissima accessions clustered close to P. tarminiana accessions. The affinity between these three species is particularly interesting for conservation and use of banana passion fruit genetic resources. All the other species formed monospecific clusters.